Korelasi Nilai Hambatan Konus Terhadap Parameter Rembesan Dalam Aplikasinya Pada Dinding Penahan Tanah - Saragi, Yetty; Bernandus, Riski; Sidabutar, Ros Anita (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2023)
Retaining walls are one of the constructions that are often found as slope safety walls which function to withstand lateral forces from the soil behind them. Retaining walls must be able to withstand shear, overturn, bearing capacity and meet the provisions of SNI 8460 2017 Geotechnical Design Requirements. The retaining wall must also be able to withstand water seepage into the soil behind it so it is necessary to know the amount of the seepage coefficient (k). The value of the seepage coefficient (k) can be determined from the Constant Head and Falling Head laboratory tests as well as by using the correlation from the results of the CPT Cone Penetration Test (which was used in this study). The CPT test was carried out at 4 stations that had experienced slope failure. Furthermore, this study designed a retaining wall in the landslide area by taking into account the magnitude of the seepage coefficient (k). From the four CPT points, the seepage coefficient values were obtained k1 = 1.06E-05 cm/sec, k2 = 5.79E-06 cm/sec, k3 = 6.77E-06 cm/sec and k4 = 6.46E-06 cm/sec. Taking into account the presence of water seepage behind the retaining wall, it is obtained that FK 1.65 still does not meet FK under conditions of high levels of uncertainty and large repair costs (FK requirements > 2.0 according to SNI 8460 2017). From this study, it was found that by calculating the seepage coefficient (k), the FK value was not sufficient and it was suggested that in its implementation, efforts to compact the soil layer by layer behind the wall were needed so that the soil behind the wall was quite dense.